2001
DOI: 10.1152/jappl.2001.91.1.425
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte counts and lymphocyte responsiveness associated with repeated bouts of strenuous endurance exercise

Abstract: This study compared leukocyte counts and lymphocyte responsiveness during and after a second bout of high-intensity endurance exercise on the same day with the response to a similar but single bout of exercise. Nine athletes participated in three 24-h trials: 1) rest in bed (Rest); 2) one bout of exercise (One); and 3) two bouts of exercise (Two). All bouts consisted of 75 min at ∼75% of maximal O2 uptake on a cycle ergometer. Lymphocytes in whole blood were stimulated with monoclonal antibodies against CD2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
3
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 52 publications
5
55
3
5
Order By: Relevance
“…Although both CD4+ and CD8+ cell counts decreased proportionally (CD4:CD8 ratio stayed similar), the %CD4+CD69+ on stimulation in vitro increased significantly. This is in contrast to the results of Ronsen et al 27 who showed no change in %CD4+CD69+ cells when determined directly after a second bout of exercise performed on the same day. Therefore, while a few acute bouts of exercise seem to have no effect on CD69 expression in CD4+ cells, many long-duration exercise bouts with additional cumulative stressors over 5 weeks resulted in significantly increased relative CD69 expression.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Although both CD4+ and CD8+ cell counts decreased proportionally (CD4:CD8 ratio stayed similar), the %CD4+CD69+ on stimulation in vitro increased significantly. This is in contrast to the results of Ronsen et al 27 who showed no change in %CD4+CD69+ cells when determined directly after a second bout of exercise performed on the same day. Therefore, while a few acute bouts of exercise seem to have no effect on CD69 expression in CD4+ cells, many long-duration exercise bouts with additional cumulative stressors over 5 weeks resulted in significantly increased relative CD69 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…25 The decreases in total lymphocyte, T-cell subpopulation, B and NK cell counts reported here, are similar to results obtained in earlier studies of endurance athletes. 1,27,32 It is known that exercise-induced increases in concentrations of stress hormones, such as catecholamines, 8 may be responsible for the exercise-induced depression of the lymphocyte counts. 3,9 Due to the nature of the game of cricket, all players are active for several hours each day when their side is bowling and fielding, and successful batsmen may also play for many hours on end, whilst those batsmen still to follow are under psychological stress.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations